Optimisation of the diesel rebate system for South African mines - Mudanalwo, Nakisani Monalisa (Stellenbosch : Stellenbosch University, 2025)
Mudanalwo, N. M. 2025. Optimisation of the diesel rebate system for South African mines. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/9bb3645c-97e3-4beb-9d72-788f9f043a29